Explicating gender disparity in wearing face masks during the COVID-19 pandemic - Kim Hoe Looi (BMC, 2022)
Abstract Background The available evidence suggests that women were more likely to wear face masks as a precaution during the COVID-19 pandemic. However, few studies have explicated this gender disparity in wearing face masks. This study investigates associations of demographic factors with wearing face masks in Malaysia during the COVID-19 pandemic, then explicates gender disparity in wearing face masks from the lens of the Protection Motivation Theory. Methods The first part of this study employed a structured online survey of 708 Malaysian adult participants. Data collected were quantitatively analyzed by means of descriptive statistics, bivariate correlations, analysis of variance (ANOVA), and multiple linear regression. The second part of this study was conducted among 28 women to better understand gender disparity in protection motivations from the perspectives of women. Results Gender has the strongest positive association with wearing face masks (p-value < .001), followed by age (p-value = .028). The Protection Motivation Theory adequately explicated the gender disparity in wearing face masks. Additionally, women were motivated to wear face masks beyond protection from the SARS-CoV-2. Conclusion Understanding the underlying motivations for wearing face masks informs design of gender-based public health messages to increase compliance with public health regulations and reduce morbidity and mortality for present and future public health crises.